Exclusivity for all - Bråkig collection by ArtRebels and Ikea - Aprea, Maria Rosaria (Prototyper – Studier i design, 2016)
The following article addresses the issue of how and why the collaboration between the Danish design group ArtRebels and Ikea can be criticised. Which message do we receive when a self-labelled “rebellious” group of young designers decides to collaborate with a giant of the marketplace? And not only a giant of the market but one that, despite the fame of commercialising democratic design in line with the Scandinavian values, notoriously exhibits an aggressive attitude toward the minor actors of the design sector, has frequently been the object of controversial disputes over plagiarism, and is accused of breaking environmental and ethical regulations?